Improving critical thinking skill of preservice chemistry teacher through writing assignment. (August 2019) - Burhanuddin,; Azizah, U; Ibrahim, M
Abstract: Critical thinking is a skill that can be trained, which has some indicators such as thinking clearly and rational, be able to evaluate an information credibly through interpretation, analysis, argumentation and making conclusion. There are three indicators that can be used to identify critical thinking skill of chemistry student, i.e. analysis, evaluation and inference. These indicators are formulated based on the chemistry subject to be learned and explicitly can be formulated in the learning plan, student activity sheet, and learning material. Through writing assignment at the end of learning phase of the Reality-based Chemistry Learning Model, students's critical thinking can be identified.